Human dimension in information system development: a case of CRM-i / Ahmad Sallehin Khalid - Khalid, Ahmad Sallehin (2011)
Customer management plays an important role and is seen as a new approach that can be used in the organization. However, there is no specific studies focus on in human dimension or insaniah approach in Customer Relationship Management (CRM). The researcher will conduct research related to the implementation of CRM-/ by using a framework that has been proposed by previous researcher. The objective of this study was to propose CRM-i Features, and to study the CRM-/ implementation of human dimension in committee at higher learning institution. The scope of the research covered 32 committees at Seri Iskandar MARA Professional College, Perak. Methodology used for this research is questionnaires and interviews. The study found that the application of human dimension element (insaniah) is crucial to be implemented within an organization and there are some suggested CRM-i features in system development. Therefore, insaniah concept approach can be suggested and applied in all public or private sector.